THE STRUCTURE OF COSTS OF ANTIEPILEPTIC THERAPY ACCORDING TO THE DATA OF CENTER FOR CHILDREN WITH EPILEPSY - E. V. Shagrova; N. V. Orekhova; M. V. Leonova; P. N. Vlasov (Русский журнал детской неврологии)
The authors analyzed the direct and indirect costs of treating epilepsy in 611 children aged from 1 month to 18 years in urban outpatient treatment and diagnostic center for the treatment of epilepsy in children based on the individual characteristics of each patient: forms of epilepsy, used regimen of therapy, effectiveness of therapy, body mass. The pharmacoeconomic aspects in idiopathic generalized epilepsy, idiopathic partial epilepsy, epileptic encephalopathies, symptomatic partial epilepsy and cryptogenic partial epilepsy were analyzed. It turned out that in patients with 50% effectiveness of treatment costs increase by more than twice, and in cases of non- effectiveness of treatment — more than three times — in all forms of epilepsy. Indirect costs in cases of loss of control for seizures exceed the direct costs saving